Language, copyright and geographic segmentation in the EU Digital Single Market for music and film - Estrella Gomez-Herrera; Bertin Martens (European Commission, Joint Research Centre (JRC), 2015)
The EU seeks to create a seamless online Digital Single Market for media products such as digital music and film. The territoriality of the copyright regime is often perceived as an obstacle that induces geographical segmentation. This paper provides empirical evidence on the extent of market segmentation in the EU on the supply and demand side and measures the contribution of several drivers of this market segmentation. We use data from the Apple iTunes country stores in 27 EU Member States to measure geographical market segmentation in supply (availability), demand (sales) and prices across the EU for downloadable digital music and film. We find that availability of EU media products across country stores in the EU is close to 80% for music and 40% for films but only 27% for EU-produced films. Recent industry initiatives to reduce the transaction costs of making digital music available across borders result in a reasonably wide availability though still short of the 100% mark. Vertical agreements in the supply chain of films remain an obstacle for wider availability of digital films. Consumer preference variables such as cultural proximity, a shared language or border and inherent preferences for home market products are the main drivers for the observed geographical market segmentation in supply and demand patterns. Supply side factors including copyright-related trade costs probably still play a role though we can only infer this indirectly in the absence of data on copyright licensing arrangements at product level. Commercial strategies in general and competition-restricting territorial agreements in film distribution in particular will also reduce availability. We also find evidence of price differentiation across iTunes EU country stores, correlated with overall country price levels.
Keywords: F15; O52; 330; digital music; online trade; music downloads; trade in cultural products; gravity model; cultural diversity